2012
DOI: 10.1089/aid.2011.0128
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Molecular Epidemiology inpoland gp41 Genes Among Naive Patients from Mato Grosso do Sul State, Central Western Brazil

Abstract: Antiretroviral naive patients (n = 49) were recruited in central western Brazil (Campo Grande City/Mato Grosso do Sul State, located across the Bolivia and Paraguay borders). HIV-1 protease (PR), reverse transcriptase (RT), and env gp41 HR1 fragments were sequenced. Genetic diversity was analyzed by REGA/phylogenetic analyses. Intersubtype recombinants were identified by SimPlot/phylogenetic trees. PR/RT resistance was analyzed by Calibrated Population Resistance/Stanford databases. T-20 resistance in gp41 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…The results presented confirmed that subtype B is still the main HIV-1 variant and concordant with data from other studies on adult and children populations from Brazil [24], [33], [34], [35]. The most remarkable observations in this study are that at least 38.1% of the 42 patients with proviral DNA sequences are infected with HIV-1 BF1 recombinant variants, which is relatively much higher if compared to earlier studies on children and adolescent patients in Brazil [33], [34], [35], [36], [37], [38]. This difference is not surprising, because small fragments from different regions of HIV genomes were characterized in the previous studies while we used larger overlapped fragments to sequence the full-length genome, which undoubtedly provides efficient discrimination of HIV subtypes and the recombinant forms.…”
Section: Discussionsupporting
confidence: 91%
“…The results presented confirmed that subtype B is still the main HIV-1 variant and concordant with data from other studies on adult and children populations from Brazil [24], [33], [34], [35]. The most remarkable observations in this study are that at least 38.1% of the 42 patients with proviral DNA sequences are infected with HIV-1 BF1 recombinant variants, which is relatively much higher if compared to earlier studies on children and adolescent patients in Brazil [33], [34], [35], [36], [37], [38]. This difference is not surprising, because small fragments from different regions of HIV genomes were characterized in the previous studies while we used larger overlapped fragments to sequence the full-length genome, which undoubtedly provides efficient discrimination of HIV subtypes and the recombinant forms.…”
Section: Discussionsupporting
confidence: 91%
“…New PR/RT subtype C sequences were obtained from 32 individuals from RJ selected from a larger cohort of about 3,000 HIV-infected patients followed at outpatient clinics from the Public Health System distributed throughout the state that underwent HIV genotyping tests at the Laboratory of AIDS and Molecular Immunology (FIOCRUZ) between 2002 and 2011, as previously described [20]. The HIV-1 subtype C pol sequences from RJ were combined with sequences from SP ( n = 18), GO ( n = 16), MT ( n = 4) and MS ( n = 4) available at the Los Álamos HIV Sequence Database ( www.hiv.lanl.gov ) and described elsewhere [10,14,15,16,17,18,21,22,23,24], and with a dataset of sequences isolated in the south region (RS = 55, SC = 41 and PR = 39) described in detail in a previous study [25]. The study was approved by the Instituto Oswaldo Cruz - Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Subtype C was observed in 6-8% of patients from the São Paulo (SP) state [9,10], 0.5-1% of patients from the Rio de Janeiro (RJ) state [11,12,13], 3-11% of patients from the Goiás (GO) state [14,15,16], 5% of patients from the Mato Grosso (MT) state [17], 10% of patients from the Mato Grosso do Sul (MS) state [18] and 6% of patients from the Tocantins state [19]. Although those studies support an influx of variants from the southern region, the exact origin and dissemination dynamics of Brazilian subtype C viruses circulating outside the southern states has not been studied in detail up to date.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were found when more than one genomic region was evaluated. [10][11][12] The sequences of all mother-child pairs were in subtype accordance, including those harboring BF recombinant strains. It is likely that the recombinants exhibit some advantages over parental strains with regard to any changes in tropism and viral fitness, making them potentially more virulent and more efficiently transmitted.…”
mentioning
confidence: 96%